Borate loaded alpha-Fe2O3 photo-anode as well as preparation method and application thereof

By forming a borate film on the α-Fe2O3 photoanode, the problems of poor conductivity and low charge transfer efficiency are solved, the photoelectrochemical performance and oxygen evolution reaction kinetics are improved, and the efficiency of photoelectrocatalytic water decomposition is improved.

CN119243232APending Publication Date: 2025-01-03CCTEG CHINA COAL RES INST
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411337572.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The poor conductivity of α-Fe2O3 photoanode, low charge transfer efficiency and high overpotential of oxygen evolution reaction limit its application efficiency in photoelectrocatalytic water decomposition.

Method used

The β-FeOOH film was grown by hydrothermal method, and converted into an α-Fe2O3 film by high-temperature annealing, and then immersed in boric acid solution and annealed at low temperature to form a borate-loaded α-Fe2O3 photoanode, which improves its conductivity and charge transport efficiency.

Benefits of technology

It effectively reduces the overpotential of the oxygen evolution reaction, improves the photoelectrochemical performance, improves the photocurrent density and monochromatic light conversion efficiency, and meets the application needs of photoelectrochemical cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243232A_ABST
    Figure CN119243232A_ABST
Patent Text Reader

Abstract

The invention provides a borate loaded alpha-Fe2O3 photo-anode as well as a preparation method and application thereof, and belongs to the technical field of material science and photoelectrocatalysis. The preparation method comprises the following steps: S1, growing a beta-FeOOH film on FTO (Fluorine-doped Tin Oxide) conductive glass by utilizing a hydrothermal method; s2, the beta-FeOOH thin film is subjected to high-temperature annealing treatment in an inert atmosphere, and an alpha-Fe2O3 thin film is obtained; and S3, the alpha-Fe2O3 thin film is put into a boric acid solution to be soaked, then the soaked alpha-Fe2O3 thin film is subjected to low-temperature annealing treatment in an inert atmosphere, a borate thin film is formed on the surface of the alpha-Fe2O3 thin film, and the borate-loaded alpha-Fe2O3 photo-anode is obtained. According to the preparation method, the problems that alpha-Fe2O3 is poor in conductivity, low in charge transfer efficiency, high in overpotential of oxygen evolution reaction and the like are solved by means of the strategies of ion doping and surface loading of borate in the step S3, the photoelectrochemical performance of alpha-Fe2O3 is improved, and the borate loaded alpha-Fe2O3 photo-anode meets the application requirement in a photoelectrochemical cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and photoelectrocatalysis technology, and specifically relates to a borate-loaded α-Fe2O3 photoanode and a preparation method and application thereof. Background Art

[0002] As an energy carrier, hydrogen energy has the advantages of wide sources, high calorific value (143KJ / g), pollution-free combustion products (H2O), and easy storage, making it one of the most promising energy sources to replace fossil energy. The many advantages of hydrogen energy determine its important strategic position in energy development, and the development of hydrogen energy economy has become the mainstream of development in the new energy era. Existing hydrogen production methods include hydrogen production from fossil energy, industrial by-product hydrogen, hydrogen production from water electrolysis, and hydrogen production from photoelectrocatalytic water decomposition. Under the trend of international low-carbon energy policies, hydrogen production from photoelectrocatalytic water decomposition has gradually developed. Photoelectrocatalytic water decomposition is to convert solar energy into a form of hydrogen energy that is easy to store and use by photoelectrocatalytic water decomposition. In this process, hydrogen is used as an energy carrier and water decomposition is used as a preparation method to realize the conversion and utilization of solar energy.

[0003] In the process of photoelectrocatalytic water splitting, the photoelectrochemical cell consists of at least one anode responsible for absorbing sunlight and a cathode used as a hydrogen evolution catalyst. The semiconductor photoanode material, as the core component of the photoelectrochemical cell, plays a decisive role in the solar-to-hydrogen energy conversion efficiency of the entire device. The band gap of the ideal photoanode electrocatalyst should span the oxidation potential and reduction potential of water splitting, that is, the valence band edge of the photocatalyst is higher than the oxidation potential (O2 / H2O), and the conduction band edge is lower than the reduction potential (H + / H2O), and the positions of the valence band and conduction band cannot deviate too much to both sides, because a large band gap will reduce the utilization rate of sunlight.

[0004] In order to achieve spontaneous solar-driven water splitting, the selection of suitable semiconductor materials is crucial for photoelectrocatalytic water splitting research. Metal oxides have been widely studied due to their advantages such as excellent chemical stability, low cost, suitable band edge position and wide band gap distribution. Among them, hematite (α-Fe2O3) semiconductor materials have a suitable band gap (~2.1eV), high theoretical photoelectric conversion efficiency, excellent chemical stability and are cheap and easy to obtain, making them very promising photoelectric materials. However, α-Fe2O3 materials also have many disadvantages as photoanodes, which limit their further application in photoelectrocatalytic water splitting. For example, single-phase α-Fe2O3 is not a good conductor of electricity and has poor conductivity. At the same time, the short pore diffusion length (2~4nm) and excited state lifetime (<10ps) hinder the rapid transfer of photogenerated electrons and holes, which easily causes carrier recombination; secondly, the slow surface oxidation kinetics lead to a higher oxygen evolution overpotential, and have a low photocurrent density at low bias, resulting in low efficiency of the entire water splitting process.

[0005] In order to solve these shortcomings, modification and modification strategies such as bulk element doping, loading of co-catalysts and surface passivation are generally adopted. For example, the morphology and structure of α-Fe2O3 materials are nano-sized to increase the effective specific surface area and improve the photoelectrocatalytic performance. Therefore, seeking more optimized modification strategies or adopting multi-level modification methods is the current research and development trend to improve the photoelectrocatalytic performance of α-Fe2O3 materials. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a borate-loaded α-Fe2O3 photoanode and a preparation method and application thereof.

[0007] A first aspect of an embodiment of the present invention provides a method for preparing a borate-loaded α-Fe2O3 photoanode, comprising the following steps:

[0008] S1. Growth of β-FeOOH thin film on FTO conductive glass using hydrothermal method;

[0009] S2, subjecting the β-FeOOH film to a high temperature annealing treatment in an inert atmosphere to obtain an α-Fe2O3 film;

[0010] S3, immersing the α-Fe2O3 film in a boric acid solution, and then annealing the immersed α-Fe2O3 film at a low temperature in an inert atmosphere to form a borate film on the surface of the α-Fe2O3 film, thereby obtaining a borate-loaded α-Fe2O3 photoanode.

[0011] The advantages and technical effects brought by the preparation method of the first aspect of the embodiment of the present invention are:

[0012] (1) The preparation method of the first aspect of the embodiment of the present invention utilizes the strategy of ion doping and surface loading of borates in step S3 to solve the problems of poor conductivity, low charge transfer efficiency and high overpotential of oxygen evolution reaction of α-Fe2O3 photoanode, thereby improving the photoelectrochemical performance of α-Fe2O3 photoanode and enabling the borate-loaded α-Fe2O3 photoanode to meet the application requirements in photoelectrochemical cells.

[0013] (2) As an oxygen evolution electrocatalyst, borates effectively reduce the overpotential of the oxygen evolution reaction of the α-Fe2O3 photoanode and improve the kinetics of the oxygen evolution reaction on the surface of the α-Fe2O3 photoanode. In addition, borates can also play a co-catalytic role, increase the active sites of the α-Fe2O3 photoanode, inhibit the surface recombination of electrons and holes, and improve the kinetics of water oxidation on the surface of the photoanode, thereby improving the photocurrent density and monochromatic light conversion efficiency.

[0014] (3) The preparation method of the first aspect of the embodiment of the present invention uses boric acid as a precursor for loading borate, and utilizes an immersion-annealing method to modify the α-Fe2O3 photoanode. The borate film in situ grown on the α-Fe2O3 film is tightly bonded to the α-Fe2O3 film, which can effectively promote the improvement of the photoelectric performance of the α-Fe2O3 photoanode.

[0015] In some embodiments, the morphology of the β-FeOOH film and the α-Fe2O3 film is a nanorod array.

[0016] In some embodiments, in step S3, the solvent used for the boric acid solution is anhydrous ethanol.

[0017] In some embodiments, in step S3, the concentration of the boric acid solution is 1.5-2.5 mol / L.

[0018] In some embodiments, in step S3, the immersion is carried out at room temperature for 3 to 15 minutes.

[0019] In some embodiments, in step S3, the low temperature annealing treatment is carried out at a holding temperature of 150 to 350° C. and a holding time of 1 to 3 hours.

[0020] In some embodiments, in step S3, after the low-temperature annealing treatment, the product after the low-temperature annealing treatment is washed and dried to obtain the borate-loaded α-Fe2O3 photoanode.

[0021] In some embodiments, in step S3, the thickness of the borate film is 3-5 nm.

[0022] A second aspect of an embodiment of the present invention provides a borate-loaded α-Fe2O3 photoanode obtained by the preparation method of the first aspect of an embodiment of the present invention.

[0023] The advantages and technical effects brought by the borate-loaded α-Fe2O3 photoanode of the second aspect of the embodiment of the present invention are:

[0024] Due to the use of the preparation method of the first aspect of the embodiment of the present invention, the borate-loaded α-Fe2O3 photoanode of the second aspect of the embodiment of the present invention has higher conductivity and charge transfer efficiency and lower oxygen evolution reaction overpotential, and has excellent photoelectrochemical performance, meeting the application requirements in photoelectrochemical cells.

[0025] The third aspect of the embodiments of the present invention provides the use of the borate-loaded α-Fe2O3 photoanode according to the second aspect of the embodiments of the present invention in photoelectrocatalytic water decomposition, photoelectrocatalytic degradation, photoelectrochemical reaction and environmental purification.

[0026] The advantages and technical effects brought about by the application of the third aspect of the embodiment of the present invention are as follows:

[0027] Since the borate-loaded α-Fe2O3 photoanode of the second aspect of the embodiment of the present invention is adopted, it can meet the application requirements in photoelectrocatalytic water decomposition, photoelectrocatalytic degradation, photoelectrochemical reaction and environmental purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a flowchart of a method for preparing a borate-loaded α-Fe2O3 photoanode according to an embodiment of the present invention.

[0029] Figure 2 It is a scanning electron microscope image of the α-Fe2O3 of comparative example 7 and the α-Fe2O3@Bi photoanode of example 1.

[0030] Figure 3 This is the transmission electron microscope image of the α-Fe2O3 photoanode of Comparative Example 7.

[0031] Figure 4 2. X-ray diffraction spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0032] Figure 5 The Raman spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1 are shown.

[0033] Figure 6 The UV-visible absorption spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0034] Figure 7 2. X-ray photoelectron spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0035] Figure 8 This is the EDS spectrum and element mapping of the α-Fe2O3@Bi photoanode of Example 1.

[0036] Fig. 9 These are the polarization curves of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0037] Fig.10 These are the stability test curves of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0038] Fig.11 2. The Mott-Schottky curves of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0039] Fig.12 The monochromatic light conversion efficiency of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0040] Fig.13 Electrochemical impedance spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1.

[0041] Fig.14 This is the transient current curve of the α-Fe2O3@Bi photoanode of Example 1.

[0042] Fig.15 This is the polarization curve of the boride-loaded α-Fe2O3 photoanode of Comparative Example 1.

[0043] Fig.16 This is the polarization curve of the boride-loaded α-Fe2O3 photoanode of Comparative Example 2.

[0044] Fig.17 This is the polarization curve of the boride-loaded α-Fe2O3 photoanode of Comparative Example 3.

[0045] Fig.18 This is the polarization curve of the boride-loaded α-Fe2O3 photoanode of Comparative Example 4.

[0046] Fig.19 This is the polarization curve of the boride-loaded α-Fe2O3 photoanode of Comparative Example 5.

[0047] Fig. 20 This is the polarization curve of the α-Fe2O3@NiBi photoanode of Comparative Example 6. DETAILED DESCRIPTION

[0048] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0049] A first aspect of an embodiment of the present invention provides a method for preparing a borate-loaded α-Fe2O3 photoanode, comprising the following steps:

[0050] S1. Growth of β-FeOOH thin film on FTO conductive glass using hydrothermal method;

[0051] S2, subjecting the β-FeOOH film to a high temperature annealing treatment in an inert atmosphere to obtain an α-Fe2O3 film;

[0052] S3, immersing the α-Fe2O3 film in a boric acid solution, and then annealing the immersed α-Fe2O3 film at a low temperature in an inert atmosphere to generate a borate film on the surface of the α-Fe2O3 film, thereby obtaining a borate-loaded α-Fe2O3 photoanode.

[0053] In the preparation method step S1 of the first aspect of the embodiment of the present invention, a β-FeOOH film is prepared by a hydrothermal method, and in step S2, an α-Fe2O3 film is obtained by high-temperature annealing. In the preparation method step S3 of the first aspect of the embodiment of the present invention, boric acid (H3BO3) is used as a precursor for loading borates, and an immersion-annealing method is used to react H3BO3 and α-Fe2O3 to generate an amorphous borate (such as FeBO3), and the borate is loaded on the surface of α-Fe2O3. As an oxygen evolution electrocatalyst, borate effectively reduces the overpotential of the oxygen evolution reaction of the α-Fe2O3 photoanode and improves the oxygen evolution reaction kinetics on the surface of the α-Fe2O3 photoanode; in addition, borate can also play a role in promoting catalysis, increasing the active sites of the α-Fe2O3 photoanode, inhibiting the surface recombination of electrons and holes, and improving the water oxidation kinetics on the surface of the photoanode, thereby improving the photocurrent density and monochromatic light conversion efficiency.

[0054] The preparation method of the first aspect of the embodiment of the present invention uses boric acid as a precursor for loading borates, and first loads the boric acid onto the surface of the α-Fe2O3 film by immersion, and then undergoes a low-temperature annealing treatment to allow the boric acid and the α-Fe2O3 film to react to in-situ grow a borate film on the α-Fe2O3 film. The in-situ grown borate film is tightly bonded to the α-Fe2O3 film, which can effectively promote the improvement of the photoelectric performance of the α-Fe2O3 photoanode.

[0055] In some embodiments, the morphology of the β-FeOOH film and the α-Fe2O3 film is a nanorod array. The β-FeOOH film of the nanorod array is prepared by a hydrothermal method, and then the α-Fe2O3 film of the nanorod array is obtained by high temperature annealing. The nanostructured material can provide a large interface area between the photocatalyst and the electrolyte, which is conducive to the transport and separation of charges, and can shorten the hole diffusion distance and improve the charge transfer efficiency, thereby improving the photoelectrochemical performance of the borate-loaded α-Fe2O3 photoanode.

[0056] In some embodiments, in step S1, FeCl3˙6H2O can be used as a precursor, a 0.1 mol / L FeCl3˙6H2O aqueous solution can be used as a precursor solution, and HCl can be used to adjust the pH of the precursor solution to 1.0-3.0.

[0057] In some embodiments, in step S1, a hydrothermal reaction may be performed at 95°C for 4 to 8 hours. After the hydrothermal growth is completed, a yellow β-FeOOH film of nanorod arrays is obtained on the FTO.

[0058] In some embodiments, in step S1, after the β-FeOOH film is obtained, the β-FeOOH film may be repeatedly rinsed with deionized water or ultrapure water to remove impurities.

[0059] In some embodiments, in step S2, the β-FeOOH film may be dried at 80-100° C. for 1.5-3 hours, and then the dried β-FeOOH film may be subjected to high temperature annealing treatment.

[0060] In some embodiments, in step S2, the inert atmosphere may be nitrogen and / or argon.

[0061] In some embodiments, in step S2, the high temperature annealing treatment can be carried out in a step-by-step heating manner. For example, the insulation temperature of the first stage is 240-260°C, and the insulation time is 25-35 minutes. The insulation temperature of the second stage is 500-600°C, and the insulation time is 1.5-2.5 hours. The insulation temperature of the third stage is 700-800°C, and the insulation time is 15-25 minutes. The heating rate is 5-10°C / min to obtain a red nanorod array α-Fe2O3 film.

[0062] In some embodiments, in step S3, the solvent used in the boric acid solution is a volatile alcohol, such as at least one of anhydrous ethanol, isopropanol and n-butanol, etc. This can ensure that the boric acid solution is green and environmentally friendly, and the waste liquid after immersion will not cause environmental pollution.

[0063] In some embodiments, in step S3, the concentration of the boric acid solution is 1.5 to 2.5 mol / L, such as 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, etc. When the concentration of the boric acid solution is too small, it is not conducive to loading a sufficient amount of boric acid by impregnation, and thus it is not conducive to loading sufficient borate during the subsequent low-temperature annealing process, which is not conducive to improving the photoelectrochemical performance of the borate-loaded α-Fe2O3 photoanode. When the concentration of the boric acid solution is too large, the boric acid loaded by impregnation may be excessive, and the morphology of the α-Fe2O3 photoanode may be destroyed during the subsequent low-temperature annealing process, which is also not conducive to improving the photoelectrochemical performance of the borate-loaded α-Fe2O3 photoanode.

[0064] In some embodiments, in step S3, the dipping is carried out at room temperature for 3 to 15 minutes, for example, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, etc. Boric acid can be loaded on the surface of the α-Fe2O3 film by dipping at room temperature, and the dipping conditions are mild. Moreover, dipping at room temperature can reduce the solvent volatilization of the boric acid solution and avoid excessive concentration of the H3BO3 solution. When the dipping time is too long, the boric acid loaded by dipping may be excessive, and the morphology of the α-Fe2O3 film may be destroyed during the subsequent low-temperature annealing treatment, which is also not conducive to improving the photoelectrochemical performance of the borate-loaded α-Fe2O3 photoanode. When the dipping time is too short, it is not conducive to loading a sufficient amount of boric acid by dipping, and it is not conducive to loading enough borates during the subsequent low-temperature annealing treatment, which is not conducive to improving the photoelectrochemical performance of the α-Fe2O3 photoanode.

[0065] In some embodiments, in step S3, the holding temperature of the low-temperature annealing treatment is 150-350°C, such as 150°C, 200°C, 250°C, 300°C, 350°C, etc.; the holding time is 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h, etc. When the holding temperature of the low-temperature annealing treatment is too low or the holding time is too short, it is not conducive to loading enough borate, thereby not conducive to improving the photoelectrochemical performance of the α-Fe2O3 photoanode. When the holding temperature of the low-temperature annealing treatment is too high or the holding time is too long, it is not conducive to reducing costs and increasing efficiency.

[0066] In some embodiments, in step S3, the inert atmosphere may be nitrogen and / or argon.

[0067] In some embodiments, in step S3, after the low-temperature annealing treatment, the product after the low-temperature annealing treatment is washed and dried to form a borate film on the surface of the α-Fe2O3 film to obtain a borate-loaded α-Fe2O3 photoanode. The washing is to remove impurities in the product after the low-temperature annealing treatment. Drying can be air-dried at room temperature or low-temperature heated drying, for example, it can be dried at a temperature greater than or equal to room temperature but less than or equal to 100°C for 1 to 3 hours.

[0068] In some embodiments, in step S3, the thickness of the borate film is 3 to 5 nm, for example, 3 nm, 3.2 nm, 3.4 nm, 3.5 nm, 3.6 nm, 3.8 nm, 4 nm, 4.2 nm, 4.4 nm, 4.5 nm, 4.6 nm, 4.8 nm, 5 nm, etc. The borate film with nanometer-scale thickness may have a certain effect on the surface morphology of the α-Fe2O3 film, for example, the top arrangement of the nanorod array α-Fe2O3 becomes more compact and smooth, which is beneficial to reduce the surface trap concentration of the photoanode and reduce carrier recombination in the process of photoelectrocatalytic water decomposition, thereby improving the photoelectrocatalytic performance of the photoanode.

[0069] A second aspect of an embodiment of the present invention provides a borate-loaded α-Fe2O3 photoanode obtained by the preparation method of the first aspect of an embodiment of the present invention.

[0070] Due to the use of the preparation method of the first aspect of the embodiment of the present invention, the borate-loaded α-Fe2O3 photoanode of the second aspect of the embodiment of the present invention has higher conductivity and charge transfer efficiency and lower oxygen evolution reaction overpotential, and has excellent photoelectrochemical performance, meeting the application requirements in photoelectrochemical cells.

[0071] The third aspect of the embodiments of the present invention provides the use of the borate-loaded α-Fe2O3 photoanode according to the second aspect of the embodiments of the present invention in photoelectrocatalytic water decomposition, photoelectrocatalytic degradation, photoelectrochemical reaction and environmental purification.

[0072] Since the borate-loaded α-Fe2O3 photoanode of the second aspect of the embodiment of the present invention is adopted, it can meet the application requirements in photoelectrocatalytic water decomposition, photoelectrocatalytic degradation, photoelectrochemical reaction and environmental purification.

[0073] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.

[0074] Example 1

[0075] The preparation method of borate-loaded α-Fe2O3 photoanode comprises the following steps:

[0076] (1) Weigh 1.50 g of FeCl3˙6H2O (analytical grade) using an electronic balance and prepare a 0.1 mol / L FeCl3˙6H2O aqueous solution with ultrapure water (≥18 MΩ˙cm).

[0077] (2) Add 35 mL of 0.1 mol / L FeCl3˙6H2O aqueous solution to the polytetrafluoroethylene liner and adjust the pH to 1.5 with 36% HCl at 25°C as a precursor solution for the hydrothermal reaction.

[0078] (3) Ultrasonic cleaning of FTO conductive glass (50×10×2 mm) was performed with acetone (analytical grade), anhydrous ethanol, and ultrapure water in turn, and the cleaned FTO conductive glass was taped with polyacetamide high temperature resistant tape to control the growth shape and position of the nanoarray (S=1.13 cm 2 ), and immerse the packaged FTO upside down into the hydrothermal reaction precursor solution.

[0079] (4) The hydrothermal reactor was placed in a programmed temperature oven and subjected to a hydrothermal reaction at 95° C. for 6 h to obtain a yellow nanoarray β-FeOOH film on the FTO, which was then repeatedly rinsed with ultrapure water to remove impurities.

[0080] (5) The β-FeOOH film was dried at 80 °C for 2 h and annealed at 250 °C / 30 min, 550 °C / 2 h, and 750 °C / 20 min in a N2 atmosphere at a heating rate of 5 °C / min to generate a red α-Fe2O3 film.

[0081] (6) Weigh a certain mass of H3BO3, prepare a 0.2 mol / L H3BO3 solution with anhydrous ethanol, immerse the prepared α-Fe2O3 film in the H3BO3 solution at 25°C for 10 min and then air-dry, anneal the immersed sample at 250°C for 2 h in a N2 atmosphere, wash the sample with excess ultrapure water to remove surface impurities, and form a borate film with a thickness of 3 to 5 nm on the surface of the α-Fe2O3 film to obtain a borate-loaded α-Fe2O3 photoanode (denoted as α-Fe2O3@Bi photoanode).

[0082] (7) The prepared borate-loaded α-Fe2O3 photoanode was connected to the copper wire and the FTO conductive surface with an appropriate amount of silver gel, the electrode was encapsulated with insulating tape and epoxy resin sealant, and the electrode was placed in a dustproof cabinet for static curing.

[0083] Example 2

[0084] The method of this embodiment is the same as that of embodiment 1, except that in step (6), annealing is performed at 150° C. for 2 h, and the thickness of the borate film is 3 to 5 nm.

[0085] Example 3

[0086] The method of this embodiment is the same as that of embodiment 1, except that in step (6), annealing is performed at 200° C. for 2 h, and the thickness of the borate film is 3 to 5 nm.

[0087] Example 4

[0088] The method of this embodiment is the same as that of embodiment 1, except that in step (6), annealing is performed at 300° C. for 2 h, and the thickness of the borate film is 3 to 5 nm.

[0089] Example 5

[0090] The method of this embodiment is the same as that of embodiment 1, except that in step (6), annealing is performed at 350° C. for 2 h, and the thickness of the borate film is 3 to 5 nm.

[0091] Comparative Example 1

[0092] The method of this comparative example is the same as that of Example 1, except that, in step (6), a certain mass of sodium borohydride is weighed, and a 0.2 mol / L sodium borohydride solution is prepared with anhydrous ethanol. The prepared α-Fe2O3 photoanode is placed in the sodium borohydride solution and immersed at 25°C for 10 min and then dried. The immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, and the sample is washed with excess ultrapure water to remove surface impurities, thereby obtaining a boride (sodium borohydride) loaded α-Fe2O3 photoanode.

[0093] Comparative Example 2

[0094] The method of this comparative example is the same as that of Example 1, except that, in step (6), a certain mass of sodium tetraborate is weighed, and a 0.2 mol / L sodium tetraborate solution is prepared with anhydrous ethanol. The prepared α-Fe2O3 photoanode is placed in the sodium tetraborate solution and immersed at 25°C for 10 min and then dried. The immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, and the sample is washed with excess ultrapure water to remove surface impurities, thereby obtaining a boride (sodium tetraborate) loaded α-Fe2O3 photoanode.

[0095] Comparative Example 3

[0096] The method of this comparative example is the same as that of Example 1, except that, in step (6), a certain mass of potassium tetraborate is weighed, and a 0.2 mol / L potassium tetraborate solution is prepared with anhydrous ethanol. The prepared α-Fe2O3 photoanode is placed in the potassium tetraborate solution and immersed at 25°C for 10 min and then dried. The immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, and the sample is washed with excess ultrapure water to remove surface impurities, thereby obtaining a boride (potassium tetraborate) loaded α-Fe2O3 photoanode.

[0097] Comparative Example 4

[0098] The method of this comparative example is the same as that of Example 1, except that, in step (6), a certain mass of potassium fluoroborate is weighed, a 0.2 mol / L potassium fluoroborate solution is prepared with anhydrous ethanol, the prepared α-Fe2O3 photoanode is placed in the potassium fluoroborate solution and immersed at 25°C for 10 min and then dried, the immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, the sample is washed with excess ultrapure water to remove surface impurities, and a boride (potassium fluoroborate)-loaded α-Fe2O3 photoanode is obtained.

[0099] Comparative Example 5

[0100] The method of this comparative example is the same as that of Example 1, except that, in step (6), a certain mass of sodium fluoroborate is weighed, a 0.2 mol / L sodium fluoroborate solution is prepared with anhydrous ethanol, the prepared α-Fe2O3 photoanode is placed in the sodium fluoroborate solution and immersed at 25°C for 10 min and then dried, the immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, the sample is washed with excess ultrapure water to remove surface impurities, and a boride (sodium fluoroborate)-loaded α-Fe2O3 photoanode is obtained.

[0101] Comparative Example 6

[0102] The method of this comparative example is the same as that of Example 1, except that in step (6), a certain mass of sodium borohydride and nickel chloride hexahydrate are weighed, and a 0.2 mol / L solution is prepared with anhydrous ethanol in a certain proportion as a precursor solution, the prepared α-Fe2O3 photoanode is placed in the precursor solution and immersed at 25°C for 10 min and then dried, the immersed sample is annealed at 250°C in a N2 atmosphere for 2 h, and the sample is washed with excess ultrapure water to remove surface impurities to obtain a boride-loaded α-Fe2O3@NiBi photoanode, which is recorded as α-Fe2O3@NiBi photoanode.

[0103] Comparative Example 7

[0104] The method of this comparative example is the same as that of Example 1, except that step (6) is omitted and the obtained photoanode is an α-Fe2O3 photoanode.

[0105] Performance Testing

[0106] 1. The characterization methods of the physical and chemical properties of the photoanode are as follows:

[0107] (1) The element content of the photoanode was determined by inductively coupled plasma atomic emission spectrometry.

[0108] (2) Raman characterization is used to determine whether the photoanode has obvious Raman characteristic peaks.

[0109] (3) X-ray diffraction is used to characterize and analyze the composition, molecular structure and morphology of the photoanode.

[0110] (4) Scanning electron microscopy and transmission electron microscopy were used to characterize the morphology and structure of the photoanode and the changes on the surface of the nanoarray.

[0111] (5) The UV-visible absorption spectrum is used to determine the absorption range of the light anode, the optical diffuse reflection characteristics, and calculate its bandgap width.

[0112] 2. The electrochemical test steps of the photoanode are as follows:

[0113] In the three-electrode test system, Pt mesh (1×1 cm) was used as the counter electrode, Ag / AgCl (saturated KCl solution) was used as the reference electrode, the photoanode was used as the working electrode, and the electrolyte was 0.1 mol / L (pH=12.6) KOH aqueous solution. In the simulated sunlight 1.5 times sunlight (AM=1.5G, light power density of 100 mW / cm 2 ). The applied bias relative to the reference electrode is converted to the bias relative to the reversible hydrogen electrode (RHE, V RHE =E Ag / AgCl +0.059pH+0.197).

[0114] (1) Linear polarization curve test: Pass high-purity N2 (99.99%) into 0.1 mol / L KOH aqueous solution for at least 30 min. Place the working electrode, AM = 1.5 G, scan range -0.4 ~ 0.7 V Ag / AgCl , scan rate 20mV / s, forward scan at 10mV / s, and record the polarization curve.

[0115] (2) Electrochemical impedance spectroscopy: High-purity N2 (99.99%) was introduced into a 0.1 mol / L KOH aqueous solution for at least 30 min. Under dark conditions, the test frequency range was 0.1 to 105 Hz at a scan rate of 10 mV / s and the applied bias range was 0 to 0.3 V. Ag / AgCl .

[0116] (3) Mott-Schottky curve test: under light conditions, test frequency 1000Hz, voltage range -0.4~0.7V Ag / AgCl , theoretically, the straight line segment fitting calculation of the measured curve is as follows:

[0117]

[0118] Where C is the capacitance of the space charge region per unit surface area (F / cm 2 ); e is the elementary charge (1.6×10 -19 C); ε≈40, is the dielectric constant of α-Fe2O3; ε0 is the dielectric constant at room temperature (8.85×10 -14F / cm; V is the external bias voltage on the photoanode; K is the Boltzmann constant (1.38×10 -23 J / K); T is the absolute temperature (K). The lower E fb It can inhibit the recombination of photogenerated holes and electrons, which is beneficial to the reduction of the opening voltage. d ) reflects the conductive properties of α-Fe2O3.

[0119] (4) Monochromatic light conversion efficiency (IPCE) test: It can also be called light-to-electricity conversion efficiency. The formula is as follows:

[0120]

[0121] J(mA / cm 2 ) is the wavelength λ(nm) and the light intensity P mono (mW / cm 2 ) is the photocurrent density measured under the condition of E g =1240 / λ0 is a rough way to calculate the band gap width of the photoanode material, where λ0 is the maximum wavelength (nm) when the external quantum efficiency is the highest.

[0122] Table 1. Comparison of performance parameters between Example 1 and Comparative Example 7

[0123]

[0124] In the embodiment of the present invention, boric acid is used as a precursor for loading borates, and an immersion-annealing method is used to modify the α-Fe2O3 photoanode, thereby improving the photoelectric performance of the α-Fe2O3 photoanode, and the catalytic mechanism of borates and their structure-activity relationship are studied.

[0125] Specifically, Example 1 effectively loads borate on the surface of α-Fe2O3 photoanode nanorod array by impregnation-annealing technology, and is used as a photoanode in photoelectrocatalytic water decomposition. Compared with the α-Fe2O3 photoanode without borate loading (Comparative Example 7), the loading of borate (oxygen evolution electrocatalyst) in Example 1 effectively reduces the overpotential of oxygen evolution reaction and improves the kinetics of oxygen evolution reaction on the surface of photoanode; in addition, borate can also play a role of co-catalysis, increase the active sites of α-Fe2O3 photoanode, inhibit the surface recombination of electrons and holes, and improve the kinetics of water oxidation on the surface of photoanode, thereby improving the photocurrent density and monochromatic light conversion efficiency.

[0126] Figure 2 The scanning electron microscope images of the α-Fe2O3 of comparative example 7 and the α-Fe2O3@Bi photoanode of example 1 are shown in FIG. Figure 2, the α-Fe2O3 photoanode of comparative example 7 exhibits a nanorod-like morphology, with a rod length of about 320nm and a diameter of about 60nm. The α-Fe2O3 nanorod array is closely arranged on the FTO to form a thin film. From the surface morphology of the α-Fe2O3@Bi photoanode of Example 1, it can be clearly observed that an ultra-thin borate film is modified on the surface of the α-Fe2O3 nanorod array. The darkening of the color of the nanorod array can further determine that the borate has a certain effect on the surface morphology of α-Fe2O3, and the top arrangement of the nanorods becomes more compact and smooth. In the process of photoelectrocatalytic water decomposition, this is conducive to reducing the surface trap concentration and reducing carrier recombination.

[0127] Figure 3 FIG. 1 is a transmission electron microscope image of the α-Fe2O3 photoanode of Comparative Example 7. Figure 3 It can be clearly seen that there are obvious lattice fringes on the α-Fe2O3 phase. After Fourier transform analysis, it is found that the lattice spacing is 0.232nm and 0.368nm, representing the (006) and (012) crystal planes of α-Fe2O3 respectively.

[0128] Figure 4 The X-ray diffraction spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1 are shown in FIG. Figure 4 In Example 1, no XRD characteristic peak of surface borate appeared, indicating that the borate on the surface of α-Fe2O3 photoanode exhibited amorphous properties.

[0129] Figure 5 The Raman spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1 are shown.

[0130] Figure 6 The UV-visible light absorption spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1 are shown in FIG. Figure 6 It can be seen that the absorbance of the α-Fe2O3 photoanode in the wavelength range below 600nm is significantly enhanced after borate loading, indicating that borate loading broadens the absorption range of the α-Fe2O3 photoanode.

[0131] Figure 7 α-Fe2O3 of Comparative Example 7 and α-Fe2O3@Bi photoanode of Example 1 are X-ray photoelectron spectra. Figure 7 It can be seen that the characteristic peaks of Fe2p, O1s, and B1s exist in Example 1, which confirms that boric acid successfully modifies the surface of the α-Fe2O3 photoanode nanoarray and forms borates on the surface.

[0132] Figure 8The EDS spectrum and element mapping diagram of the α-Fe2O3@Bi photoanode of Example 1 are shown in FIG. Figure 8 It can be seen that the sample of Example 1 contains B, O, Fe, and Sn elements. The Sn element diffuses from the FTO (SnO2) substrate into the α-Fe2O3 crystal structure during the high-temperature annealing process to form α-Fe2O3. The uniform distribution of the B element indicates the successful modification of α-Fe2O3 by boric acid, and it is possible to form a borate film on the surface of α-Fe2O3.

[0133] Fig. 9 α-Fe2O3@Bi photoanode of comparative example 7 and α-Fe2O3@Bi photoanode of example 1 are shown in FIG. Fig. 9 , the cyclic voltammetry curve was tested in 0.1 mol / L KOH solution under AM1.5G illumination. When the immersion time was 10 min and the annealing temperature was 250 °C, the photocurrent density of the α-Fe2O3@Bi photoanode of Example 1 was 1.23 V RHE The maximum value reached is 1.25mA / cm under applied bias 2 , and the starting potential is the lowest, indicating that the prepared boride-loaded α-Fe2O3 photoanode material has excellent photoelectrocatalytic performance.

[0134] Fig.10 The stability test curves of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1 are shown. After the α-Fe2O3 photoanode of Example 1 is impregnated with boric acid and successfully loaded with borate, the photoelectrocatalytic reaction stability of the photoanode is significantly better than that of the α-Fe2O3 photoanode of Comparative Example 7.

[0135] Fig.11 α-Fe2O3@Bi photoanode of comparative example 7 and α-Fe2O3@Bi photoanode of example 1 are Mott-Schottky curves. Fig.11 The slopes of the curves are all positive, which can be attributed to the fact that α-Fe2O3 photoanode is an n-type semiconductor. The slopes of the bare α-Fe2O3 and α-Fe2O3@Bi photoanode curves decrease in turn, indicating that N d This indicates that the surface brown loading of Example 1 can promote the charge transfer at the interface between the semiconductor and the electrolyte, increase the carrier concentration, and further improve the photocurrent density.

[0136] Fig.12 The monochromatic light conversion efficiency of the α-Fe2O3 in comparative example 7 and the α-Fe2O3@Bi photoanode in example 1 is shown in FIG. Fig.12At λ=340nm, the monochromatic light conversion efficiency of the α-Fe2O3@Bi photoanode of Example 1 is also higher than that of the α-Fe2O3 photoanode of Comparative Example 7, further proving that the α-Fe2O3@Bi photoanode of Example 1 has a wider photon absorption range and more effective photon absorption efficiency.

[0137] Fig.13 : The electrochemical impedance spectra of the α-Fe2O3 of Comparative Example 7 and the α-Fe2O3@Bi photoanode of Example 1. Fig.13 The structure-activity relationship and mechanism of each component of the photoanode were analyzed by calculating the impedance value through simulating the impedance circuit diagram. The bulk charge transfer resistance (R ct,bulk ) is significantly reduced to 323.1Ω, which is significantly lower than the α-Fe2O3 photoanode (988.9Ω) of Comparative Example 7, which further illustrates that borates can promote the transfer and separation efficiency of charges and exhibit better conductive properties.

[0138] Fig.14 is the transient current curve of the α-Fe2O3@Bi photoanode of Example 1. Fig.14 , at 1.23V RHE The photocurrent transient curve was measured below, indicating that the α-Fe2O3@Bi photoanode of Example 1 has excellent photoelectric response capability.

[0139] Table 2. Polarization curve process parameter optimization table of α-Fe2O3@Bi photoanode of Examples 1 to 5

[0140] Low temperature annealing temperature <![CDATA[1.23V RHE Current density]]> 150℃ <![CDATA[0.89mA / cm 2 ]]> 200℃ <![CDATA[1.18mA / cm 2 ]]> 250℃ <![CDATA[1.25mA / cm 2 ]]> 300℃ <![CDATA[1.20mA / cm 2 ]]> 350℃ <![CDATA[1.18mA / cm 2 ]]>

[0141] It can be seen from Table 2 that the low-temperature annealing temperature is between 150 and 350° C., and a good-performance α-Fe2O3@Bi photoanode can be obtained. Preferably, the low-temperature annealing temperature is between 200 and 350° C.

[0142] Fig.15 This is the polarization curve of the boride (sodium borohydride) loaded α-Fe2O3 photoanode in Comparative Example 1. In Comparative Example 1, sodium borohydride was used as a precursor to form a photoanode loaded with boride on α-Fe2O3. The cyclic voltammetry curve was tested in AM 1.5G, 0.1mol / L KOH solution. The photocurrent density was 1.23V RHE 0.54mA / cm under applied bias 2 , indicating that the boride (sodium borohydride) loaded α-Fe2O3 photoanode prepared with sodium borohydride as a precursor did not significantly improve the photoelectrocatalytic performance of the α-Fe2O3 photoanode material.

[0143] Fig.16This is the polarization curve of the boride (sodium tetraborohydride) loaded α-Fe2O3 photoanode of Comparative Example 2. In Comparative Example 2, sodium tetraborate is used as a precursor to form a photoanode loaded with boride on α-Fe2O3. The cyclic voltammetry curve is tested in AM 1.5G, 0.1mol / L KOH solution. The photocurrent density is 1.23V RHE 0.42mA / cm under applied bias 2 , indicating that the boride (sodium tetraborate) loaded α-Fe2O3 photoanode prepared with sodium tetraborate as a precursor inhibits the photoelectrocatalytic performance of the α-Fe2O3 photoanode material.

[0144] Fig.17 This is the polarization curve of the boride (potassium tetraborate) loaded α-Fe2O3 photoanode of Comparative Example 3. In Comparative Example 3, potassium tetraborate is used as a precursor to form a photoanode loaded with boride on α-Fe2O3. The cyclic voltammetry curve is tested in AM 1.5G, 0.1M KOH solution. The photocurrent density is 1.23V RHE 0.38mA / cm under applied bias 2 , indicating that the boride (potassium tetraborate) loaded α-Fe2O3 photoanode prepared with potassium tetraborate as a precursor inhibits the photoelectrocatalytic performance of the α-Fe2O3 photoanode material.

[0145] Fig.18 This is the polarization curve of the boride potassium fluoroborate loaded α-Fe2O3 photoanode of Comparative Example 4. In Comparative Example 4, potassium fluoroborate is used as a precursor to form a photoanode on α-Fe2O3 loaded boride. The cyclic voltammetry curve is tested in AM 1.5G, 0.1mol / L KOH solution. The photocurrent density is 1.23V RHE 0.49mA / cm under applied bias 2 , indicating that the boride (potassium fluoroborate) loaded α-Fe2O3 photoanode prepared with potassium fluoroborate as a precursor did not significantly improve the photoelectrocatalytic performance of the α-Fe2O3 photoanode material.

[0146] Fig.19 This is the polarization curve of the boride (sodium fluoroborate) loaded α-Fe2O3 photoanode of Comparative Example 5. In Comparative Example 5, sodium fluoroborate is used as a precursor to load boride on α-Fe2O3 to form a photoanode. The cyclic voltammetry curve is tested in AM 1.5G and 0.1 mol / L KOH solution. The photocurrent density is 1.23V RHE 0.45mA / cm under applied bias 2 , indicating that the boride (sodium fluoroborate) loaded α-Fe2O3 photoanode prepared with sodium fluoroborate as a precursor inhibits the photoelectrocatalytic performance of the α-Fe2O3 photoanode material.

[0147] Fig. 20This is the polarization curve of the α-Fe2O3@NiBi photoanode of Comparative Example 6. In Comparative Example 6, sodium borohydride and nickel chloride hexahydrate were used as precursors to load borate (NiBi) on α-Fe2O3 to form a photoanode. The cyclic voltammetry curve was tested in AM 1.5G and 0.1mol / L KOH solution. The photocurrent density was 1.23V RHE 0.95mA / cm under applied bias 2 , which is significantly lower than that in Example 1. This is because, in Comparative Example 6, sodium borohydride reacts only with nickel chloride hexahydrate, but not with α-Fe2O3. On the one hand, the type of borate (denoted as NiBi) generated is different from that of the borate (denoted as Bi) generated in Example 1. On the other hand, the binding between NiBi and α-Fe2O3 is not as tight as that between Bi and α-Fe2O3 in Example 1.

[0148] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0149] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a borate-loaded α-Fe2O3 photoanode, characterized in that: The following steps are involved: S1. Growth of β-FeOOH thin film on FTO conductive glass using hydrothermal method; S2, subjecting the β-FeOOH film to a high temperature annealing treatment in an inert atmosphere to obtain an α-Fe2O3 film; S3, immersing the α-Fe2O3 film in a boric acid solution, and then annealing the immersed α-Fe2O3 film at a low temperature in an inert atmosphere to form a borate film on the surface of the α-Fe2O3 film, thereby obtaining a borate-loaded α-Fe2O3 photoanode.

2. The preparation method according to claim 1, characterized in that: The morphology of the β-FeOOH film and the α-Fe2O3 film is a nanorod array.

3. The preparation method according to claim 1, characterized in that: In step S3, the solvent used in the boric acid solution is anhydrous ethanol.

4. The preparation method according to claim 1, characterized in that: In step S3, the concentration of the boric acid solution is 1.5-2.5 mol / L.

5. The preparation method according to claim 1, characterized in that: In step S3, the mixture is immersed at room temperature for 3 to 15 minutes.

6. The preparation method according to claim 1, characterized in that: In step S3, the low temperature annealing treatment is carried out at a holding temperature of 150 to 350° C. and a holding time of 1 to 3 hours.

7. The preparation method according to claim 1, characterized in that: In step S3, after the low-temperature annealing treatment, the product after the low-temperature annealing treatment is washed and dried to obtain the borate-loaded α-Fe2O3 photoanode.

8. The preparation method according to claim 1, characterized in that: In step S3, the thickness of the borate film is 3-5 nm.

9. A borate-loaded α-Fe2O3 photoanode, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the borate-loaded α-Fe2O3 photoanode according to claim 9 in photoelectrocatalytic water decomposition, photoelectrocatalytic degradation, photoelectrochemical reaction and environmental purification.

Citation Information

Cited By

  • Fe2O3 / Nd composite photo-anode and preparation method thereof

    CN119877018A

  • Phosphorus-doped carbon nitride composite bismuth vanadate photoelectrode loaded with nickel borate and preparation method of phosphorus-doped carbon nitride composite bismuth vanadate photoelectrode

    CN120026360A

  • A phosphorus-doped carbon nitride composite bismuth vanadate photoelectrode loaded with nickel borate and its preparation method.

    CN120026360B